Recording the high efficient diffraction gratings by using He-Cd laser - Kostyukevych, S.A.; Morozovska, A.N.; Minko, V.I.; Shepeliavyi, P.E.; Kudryavtsev, A.A.; Rubish, V.M.; Rubish, V.V.; Tverdokhleb, I.V.; Kostiukevych, A.S.; Dyrda, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
High efficient holographic diffraction gratings with spatial frequencies from 600 to 3600 mm⁻¹ have been recorded using As₄₀S₆₀–хSeх (х = 0, 10, 20) photoresist layers and He-Cd laser operating at the wavelength λ = 440 nm. The investigation of the grating relief made by atomic force microscopy revealed that As₄₀S₆₀–хSeх resists allows one to record grating originals with profiles of various heights depending on the resist chemical composition, its etching and exposure times. We obtained typical spectral and angular dependences of the first order diffraction efficiency for the grating with the high modulation depth and groove profile close to the sinusoidal one. Comparing the recorded gratings with different spatial frequencies, exposure and etching times, we determined optimal recording conditions (exposure and etching times) in order to obtain gratings with the high diffraction efficiency.